Reducing European Dependence on Russian Gas – distinguishing natural gas security from geopolitics - Stern, J; Rogers, H; Yafimava, K; Pirani, S; El-Katiri, L; Honore, A; Henderson, J; Hassanzadeh, E; Dickel, R (Oxford Institute for Energy Studies, 2014)
There is limited scope for significantly reducing overall European dependence on Russian gas before the mid-2020s. Countries in the Baltic region and south eastern Europe which are highly dependent on Russian gas, and hence extremely vulnerable to interruptions, could substantially reduce and even eliminate imports of Russian gas by the early 2020s, by a combination of LNG and pipeline gas from Azerbaijan. Similar measures could reduce (but not eliminate) the dependence of central Europe and Turkey on Russian gas. However, Russian gas will be highly competitive with all other pipeline gas and LNG (including US LNG) supplies to Europe, and Gazprom’s market power to impact European hub prices may be considerable. Countries with strong geopolitical fears related to Russian gas dependence will need to either terminate, or not renew on expiry, their long term contracts with Gazprom.